A imagem inalcançável do todo coleções, museus, arquivos em Italo Calvino: coleções; museus; arquivos em Italo Calvino - Cláudia Cristina Maia (2013)
This thesis aims at investigating how the collection and other cataloguing and classifying models, such as the series, museum and the archive, are shown in the work of Italo Calvino. Considering the collection as a theme and as a method, some of Calvinos works are constituted from a poetic collecting which, at the same time that it seems to want to impose an order to the world and to knowledge, tends to register the extraordinary and unique. This poetic collecting is intimately linked to the multiplicity concept developed by the writer in Six proposals for the next millennium. Based on this concept, a discussion about the continuity and discontinuity in some of Calvinos texts was presented, prioritizing in this sense, the monstrous and the residual in Sand collection. With his multiple literatures, the writer tried to discuss the fragmentation of the world and the language, in infinite narrative possibilities.